High Levels of Satisfaction and Adequate Patient-Reported Outcomes After Operative Reconstruction of Multiligament Knee Injury With Allograft Among Patients Aged 40 Years and Older - Alexander J. Toppo, M.D., M.P.H; Gabriel S. Perrone, M.D; Stephen M. Sylvia, M.D; Benjamin H. Miltenberg, B.A; Liam H. Power, B,A; John C. Richmond, M.D; Matthew J. Salzler, M.D (Elsevier, 2023)
Purpose: To describe injury characteristics and patient-reported outcomes (PROs) among patients aged 40 years and older who underwent allograft reconstruction for multiligament knee injury (MLKI). Methods: Records of patients aged 40 years and older who underwent allograft multiligament knee reconstruction at a single institution between 2007 and 2017 with a minimum of 2 years of follow-up were retrospectively reviewed. Demographic information, concomitant injuries, patient satisfaction, and PROs including International Knee Documentation Committee and Marx activity scores were obtained. Results: Twelve patients were included with a minimum follow-up time of 2.3 years (mean, 6.1; range, 2.3-10.1 years) and a mean age at surgery of 49.8 years. Seven patients were male, and the most common mechanism of injury was sport-related. The most frequently reconstructed MLKIs were anterior cruciate ligament and medial collateral ligament (4), anterior cruciate ligament and posterolateral corner (2), and posterior cruciate ligament and posterolateral corner (2). The majority of patients reported satisfaction with their treatment (11). Median International Knee Documentation Committee and Marx scores were 73 (interquartile range, 45.5-88.0) and 3 (interquartile range 0-5), respectively. Conclusions: Patients aged 40 years and older can expect a high level of satisfaction and adequate PROs at 2-years follow-up after operative reconstruction for a MLKI with allograft. This demonstrates that allograft reconstruction for a MLKI in older patients may have clinical utility. Level of Evidence: IV, therapeutic case series.